Focal radiation therapy for limited brain metastases is associated with high rates of local control and low subsequent whole brain radiation therapy. Issue 4 (5th March 2019) - Or, Michelle; Jayamanne, Dasantha; Guo, Lesley; Stevens, Mark; Parkinson, Jonathon; Cook, Raymond; Little, Nicholas; Back, Michael
Abstract : Background: Assess clinical outcomes of focal radiotherapy (RT) in patients with limited brain metastasis (LBM) with whole brain RT (WBRT) avoidance. Methods: Patients diagnosed with LBM were entered into a database between January 2010 and February 2017. Patients were recommended WBRT avoidance with focal therapy and three‐monthly magnetic resonance imaging. The primary endpoint was overall survival. Secondary endpoints included progression‐free survival, initial‐site failure (ISF), distant brain relapse (DBF), leptomeningeal disease and rate of WBRT. Analysis involved Kaplan–Meier survival estimate with log‐rank tests and Cox‐regression analysis. Results: One hundred and sixty‐six patients were managed with median follow‐up of 13 months and median overall survival of 15 months (95% confidence interval (CI) 10.8–19.2). Eighty‐three patients had central nervous system (CNS) relapse with median progression‐free survival of 11 months (95% CI 6.7–15.3), of which most failures were DBF (83.1%) with 27 ISF (32.5%). Of the ISFs, 12 (43%) had surgery alone, six had chemotherapy alone and nine received RT. Surgery or chemotherapy alone compared with RT had a significantly higher incidence of ISF with a hazard ratio of 4.96 ( P < 0.0001, 95% CI 2.10–11.83) and 6.54 ( P = 0.001, 95% CI 2.26–18.87), respectively. WBRT was utilized in only 24 patients, with 83% patients free of WBRT at 12 months. On univariate analysis, number of metastases ( P = 0.04), symptomatic extracranial disease ( P = 0.04) and early CNS relapse within 6 months ( P < 0.01) had worse survival. No grade 3–4 toxicity events were noted in 129 patients undergoing RT. Conclusion: Focal RT has a low rate of ISF with low toxicity in patients with LBMs. CNS progression was mainly DBF with low rates of salvage WBRT. Abstract : Oligometastatic brain metastasis can be treated with focal radiotherapy safely. Radiotherapy toxicity is low with focal brain radiotherapy. Rates of neurological death and whole brain radiotherapy are acceptably low with focal therapies.